Faktor-faktor yang mempengaruhi Culture shock pada mahasiswa baru angkatan 2008 PSIK FK UGM - Novianti, Devi; Warsini, Sri; Suriyanto, Rusyad Adi (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2009)
Please refer to the file